Characterization and fine mapping of RTMS10, a semi-dominant reverse thermo-sensitive genic male sterile locus in rice - Jin-long NI; De-zheng WANG; Da-hu NI; Feng-shun SONG; Jian-bo YANG; Da-nian YAO (Journal of Integrative Agriculture, 2022)
The discovery and application of environment-sensitive genic male sterile (EGMS) rice germplasm provide an easy method for hybrid rice breeding and have made great contributions to hybrid rice production. Typically, the photoperiod- and thermo-sensitive GMS (P/TGMS) lines utilized in two-line hybrid systems are male sterile under long day or/and high temperature but fertile under short day or/and low temperature conditions. However, YannongS (YnS), a reverse TGMS (rTGMS) line, is sterile under low temperature (<29°C) and fertile under high temperature (>29.5°C). Here, we report a genetic study on the rTGMS trait in YnS. Interestingly, the F1 plants of the cross between YnS and a cultivar, L422, were male sterile at 22°C and completely fertile at 27°C. Moreover, the segregation ratio of fertile and sterile individuals in YnS/L422 F2 populations changed from 1:3.05 to 2.95:1 when the ambient temperature increased, showing that the rTGMS trait exhibits semi-dominance in YnS. We further found a locus on chromosome 10, termed RTMS10, which controls the rTGMS trait in YnS. We then finely mapped RTMS10 to a ∼68 kb interval between markers ID13116 and ID1318 by YnS/L422 BC6F2 populations. A near iso-genic line (NIL) NL1 from the BC6F3 generation was developed and the pollen of NL1 became abnormal from the meiosis stage under low temperature. In summary, we identified an rTGMS locus, RTMS10, and provided co-segregated markers, which could help to accelerate molecular breeding of rTGMS lines and better understand the rTGMS trait in rice.